2020
DOI: 10.3389/fnagi.2020.00064
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Functional Hippocampal Changes in Subjective Cognitive Decline From the Community

Abstract: Background: Recently, subjective cognitive decline (SCD) has been described as the earliest at-risk state of Alzheimer's disease (AD), and drawn attention of investigators. Studies suggested that SCD-community individuals may constitute a more vulnerable population than SCD-clinic patients, therefore, to investigate the early changes of the brain may provide guidance for treatment of the disease. We sought to investigate the changes of structure and functional connectivity alternation of the hippocampus in ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
28
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 55 publications
1
28
1
Order By: Relevance
“…however, in our study we only found fusiform atrophy in subjects with AD. In addition, previous studies have identi ed that individuals with SCD showed structural gray matter volume reductions and cortical thinning in the bilateral entorhinal cortex, medial temporal, and frontotemporal regions compared to cognitively normal elders [14,38], however, there was still previous study have found no gray matter differences in SCD compared to controls [39]. we did not nd regional grey matter volume differences between SCD and NC in this study.…”
Section: Discussioncontrasting
confidence: 73%
“…however, in our study we only found fusiform atrophy in subjects with AD. In addition, previous studies have identi ed that individuals with SCD showed structural gray matter volume reductions and cortical thinning in the bilateral entorhinal cortex, medial temporal, and frontotemporal regions compared to cognitively normal elders [14,38], however, there was still previous study have found no gray matter differences in SCD compared to controls [39]. we did not nd regional grey matter volume differences between SCD and NC in this study.…”
Section: Discussioncontrasting
confidence: 73%
“…A recent neuroimaging meta-analytic study divulged that the left hippocampus comprised the anterior emotional region (HIPe), middle cognitive region (HIPc), and posterior perceptual region (HIPp) based on its neurofunctional topography [ 12 ]. In addition, several studies have revealed that HIPsub topography is pathologically involved in preclinical AD [ 11 , 14 , 15 ]. It was also recently reported that SCD exhibited structural and functional alterations in the hippocampus [ 3 , 10 , 11 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Neuroimaging evidences have consistently indicated a functional heterogeneity in hippocampus subregions (HIPsub) [13][14][15]. Furthermore, several studies have indicated that HIPsub have a selective topography of pathological involvement in preclinical AD [12,15,16]. Recently, several studies have reported that SCD present the structural and functional alterations of hippocampus [3,[10][11][12]16].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, several studies have indicated that HIPsub have a selective topography of pathological involvement in preclinical AD [12,15,16]. Recently, several studies have reported that SCD present the structural and functional alterations of hippocampus [3,[10][11][12]16]. Converging evidences suggest that SCD may present differently altered patterns of HIPsub network connectivity.…”
Section: Introductionmentioning
confidence: 99%